IS ONLINE TEACHING THE WAY OF FUTURE? (British Journal of Global Ecology and Sustainable Development, 2023)
In the 21st century, technology has transformed nearly every aspect of our lives, including education. Online teaching is becoming increasingly popular as a way to deliver education to students, Due to COVID-19 pandamic (as going outside or attending offline to educational institutions is banned), way of online education has become more prevalent than ever before.